Evaluation of symptoms of stress and quality of life of medicine students from alto sertão paraibano (Research, Society and Development, 2020)
Objective: Correlate quality of life, perception of stress, and sociodemographic aspects of medical students. Methodology: This is an epidemiological, descriptive, cross-sectional, analytical, and quantitative study. The research was carried out at Faculdade Santa Maria, in the municipality of Cajazeiras - PB. The sample population consisted of medical students, regularly enrolled in the 2019.1 periods, excluding repeat students, absenteeism, and those entitled to maternity leave. In-room questionnaires were applied with the following bases: sociodemographic questionnaire, Perceived Stress Scale (PSS-14), and the WHOQOL-brief instrument, to assess the quality of life. Results: Analyzing the quality of life and occupational stress studied, we obtained a total of 90 respondents. Mostly male and with a high purchasing power, in line with the traditional history of medical training. In terms of quality of life, we observed that men have better parameters about the physical and psychological domains and that this fact has a direct correlation with the practice of physical activities. Another important correlation was that students who sleep poorly have a worse quality of life. Regarding the perception of stress, 45.6% of medical students had an average level of perceived stress. Conclusion: Medical students are susceptible to the pathological development of stress and physical exercise routines, as well as pedagogical attempts to ease the intensive collection can help in the training of these professionals.